Effect of Seeding Rate and Nitrogen Fertilization on Growth and Yield of Sidi Misri 1 Wheat Cultivar (Triticum aestivum L.) - SOROUR, F. A.; EL-SHARKAWY, M. A.; SHAALAN, M. I. (The Libyan Journal of Agriculture, 2023)
The effect of seeding rate under different nitrogen levels on growth and yield of ‘Sid i Misri 1’ wheat cultivar. Triticum aestivum L., was studied under the field conditions of Alfateh University Farm in the 1974-1975 season. Plant height, spike length and the number of tillers and spikes per plant were increased by increasing the nitrogen level and decreasing the seeding rate. Total yield (grain plus straw), grain yield, and straw yield were increased by increasing nitrogen level as well as seeding rate. On the other hand, the harvest index (percent grain to total yield) was not significantly affected by either nitrogen level or seeding rate. On plant basis, the grain yield per plant was increased due to increasing nitrogen level, whereas it was reduced by increasing the seeding rate. The number of grains per plant and per spike were not significantly affected by nitrogen level, but were decreased by increasing the seeding rate. The number of grains/m2 was significantly increased by increasing the nitrogen level. On the other hand, no response was noted due to the seeding rate. A high significant interaction was obtained between the nitrogen level and seeding rate with respect to the number of grains/m2. The maximum number of grains/m2 resulted from the combination of the highest nitrogen level (200 kg N/ha)and the highest seeding rate(140 kg/ha). This coincided with the highest total yield (grain plus straw). Grain size (weight of 1,000 grains) was not significantly affected by the nitrogen level, but it was generally increased by increasing the seeding rate.